Learning to teach in post-apartheid South Africa Student Teachers' Encounters with Initial Teacher Education - Sayed, Yusuf (African Sun Media, 2018)
Teacher education programmes seek to provide student teachers with the knowledge and expertise to provide qualtiy teaching and learning in a diverse and challenging school context. Learning to Teach in post-apartheid South Africa: Student Teachers' Encounters with Initial Teacher Education addresses the complexities of teacher education programmes in preparing students to teach. It adds to the knowledge about teacher education, contributing critical understanding of education and the schooling system. The book provides important insights to deepen researchers, academics, teacher education providers, policy-makers, and students' understanding of the importance to address equity, redress, and quality in South African educaiton in a post-apartheid era. This book further helps to build student teachers' capacities to work creatively and to become active and critical agents of transformation. It ultimately outlines the challenges face in designing and delivering successful Inital Teacher Education programmes, and the impact this has on delivering equitable and qualtiy education.